Enhancement of biodiesel yield from a halophilic green microalga isolated under extreme hypersaline conditions through stepwise salinity adaptation strategy. (August 2020) - Abomohra, Abd El-Fatah; El-Naggar, Amal H.; Alaswad, Saleh O.; Elsayed, Mahdy; Li, Mei; Li, Wenyuan
Graphical abstract: Highlights: A new halophilic Dunaliella salina KSA-HS022 was isolated from hypersaline lagoon. Stepwise adaptation showed the highest biomass productivity of 0.191 g −1 L −1 d −1 at 125‰. Oxidative stress markers of the control were significantly higher than the adapted. Adapted culture showed the highest FAMEs productivity of 50.3 mg L −1 d −1 at 150‰. Stepwise adaptation enhanced the biodiesel yield and characteristics. Abstract: In the present study, a halophilic microalgal species was isolated from a hypersaline lagoon with salinity average of 45.3‰ and identified as Dunaliella salina KSA-HS022. It was further cultivated at a salinity range of 50–250‰, applied directly to batch cultures or through stepwise increase in a semi-continuous culture. The later showed the highest biomass productivity of 0.191 g L −1 d −1 at 125‰, which represented 45.8% higher than the corresponding batch culture (control). Oxidative markers in the control cultures were significantly higher than those of the adapted culture, confirming reduction of oxidative stress by adaptation. In addition, stepwise adaptation showed the highest lipid productivity of 56.5 mg L −1 d −1 at 150‰ (39.9% higher than the corresponding control), which resulted in the highest fatty acid methyl esters productivity. Moreover, stepwise increase of salinity up to 150‰ enhanced the biodiesel characteristics, offering a new route for enhanced biodiesel production at extraordinary salinity levels.